ISLAM DAN FUNDAMENTALISME DALAM AL’QUR’AN - Nanda Alfiyah Nur‘aulia; Neng Isma Nur Holifah; Nur Fajriyah Amini; Salis Nur Rois Kamil (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This paper examines deeper understanding of the issue of fundamentalism, especially fundamentalism in Islam. This paper discusses the meaning of fundamentalism, its history, the relationship between fundamentalism and religion, as well as problems arising from the fundamentalist movement. In addition, this paper also contains a review of the Koran on the fundamentalist movement. The method used in this study is library research by applying the maudhu'i interpretation method to find and understand the related verses. Thus, this research produces an understanding that fundamentalism has two sides, namely positive if it is applied in the right way, and negative if it is wrong in its application, especially in matters of faith; verses related to the issue of fundamentalism are taken from the word al-Ghuluw which is contained in QS. An-Nisa : 171 and Al-Maidah : 77 ; Fundamentalism begins with Christians who continue to develop in increasingly modern times; There are many extreme movements of fundamentalism that have given rise to religious conflicts.